Pelaksanaan Denda Tilang Terhadap Anak Oleh Satlantas Polresta Padang - Nurlinda Yenti; Rahmat Efendi (Fakultas Hukum Universitas Tamansiswa Padang, 2026)
Traffic violations committed by children that disrupt public welfare in the use of roads and transportation are common. Traffic violations are mostly committed by children in junior high and high school. The problem is how the Padang Police Traffic Unit applies traffic fines to children, what obstacles the Padang Police Unit experiences in applying traffic fines to children, and what are the solutions. The research method used is a descriptive sociological juridical method. The data used are primary and secondary data. The results of the study explain that the implementation of traffic fines begins when officers stop drivers suspected of being children. After a traffic stop, the Traffic Police will inspect documents such as a driver's license (SIM) or vehicle registration (STNK). If the vehicle is not in possession, the Traffic Police will temporarily impound the vehicle until the parents arrive, or the Traffic Police will issue a ticket directly, providing proof of the ticket. Challenges include a lack of legal awareness among children. One of the requirements is a driver's license (SIM). During ticketing, many drivers stop on the shoulder of the road and even make a U-turn to avoid inspections. Solutions include conducting traffic education programs in schools, participating in school activities, and conducting regular enforcement operations in schools. To mitigate these challenges, it is essential to educate schoolchildren about traffic regulations. Parents play a crucial role in their children's development, and therefore, parents should provide increased supervision.